The role of parenting and parental criticism on the body image and alexithymia during adulthood and emerging adulthood - Pellerone, Monica; Martinez Torvisco, Juan; Velianna Scaduto, Elena; Pistillo, Maria (Advances in Social Sciences Research Journal, 2021)
Literature underline that the perception of parents as strongly critical can influence the tendency to self-criticize and, as a consequence, to be more vulnerable in manifesting problems in the developmental and adulthood age, such as the risk of dropouts and relapses in the eating disorders, negative results in the worsening of anxiety disorders, the possible presence of alexithymia or obsessive compulsive disorder. The purposes of the present study was to investigate the possible influence of parenting style and parental criticism on both the body image construct (body care, body protection, and comfort in touch) and the possible presence of alexithymia in a group of Italian adolescents and adults. The present study was conducted on a group of 140 subjects, aged between 19 and 36 (M = 24.71; SD = 5.11), of which 59 men (42.1%) and 81 women (57.9%). The participants were assigned to complete the following questionnaires: Parental Bonding Instrument, Twenty-Item Toronto Alexithymia Scale, Perceived Criticism Inventory, and Body Checking Questionnaire. The results of this study support the research hypothesis that low age, a high level of paternal control and parental criticism can predict a high level of difficulty in communicating feelings. Furthermore, the importance attributed to appearance can be predicted by multiple variables, such as gender, age, mother care, father control and parental hypercriticism.